PROTOTIPE SISTEM KONTROL POM MINI BERBASIS ARDUINO - Ninda Puspita; Fauzan Andika Putra; Ocsirendi; Indra Dwisaputra (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Oil refueling stations can be divided into 2 scales, namely on a large scale managed by large companies and on a small scale managed by small shop owners. However, we still find fuel oil sellers who still use manual tools and of course are not accurate in calculating the volume of fuel oil output. One of the reasons for selling fuel oil is still using manual tools, due to limitations in the cost of purchasing tools that have been developed. Therefore, the purpose of this final project is to create an alternative tool for selling fuel oil with relatively cheaper financing than those on the market. In the implementation of this final project using water as an experimental object with the method used is to compare the suitability of the price with the volume of water issued and calculated through the water flow sensor YF-S201. The results obtained from testing the Arduino-based mini pom control system with an error percentage of 3.84% using 4 varying prices as a test.